Is dermoscopy a good tool for the diagnosis of lentigo maligna and lentigo maligna melanoma? A meta-analysis - Carapeba, Murilo de Oliveira Lima (Clin Cosmet Investig Dermatol, 2019)
Introduction: Dermoscopy is a low-cost examination performed by a dermatologist and good for the diagnosis of pigmented lesions. However, dermoscopy diagnosis of lentigo maligna (LM) and lentigo maligna melanoma (LMM) is still questionable. The objective of this study was to evaluate whether dermoscopy is an effective diagnostic method to diagnose LM/LMM from other pigmented skin lesions, and to identify which are the most frequent dermoscopic criteria associated with LM/LMM Methods: For this systematic review and meta-analysis, we used the following descriptors: dermoscopy, lentigo maligna, lentigo maligna melanoma, histopathology; and the following databases to search for articles: Cochrane Collaboration, MEDLINE; PMC (PubMed Central) - NIH (National Institutes of Health), EMBASE (The Excerpt Medical Database), and SCISEARCH, from inception to March 30, 2018. The evaluation of studies was performed using the QUADAS (Quality Assessment of Diagnostic Accuracy Studies)-2 tool. The PRISMA (Preferred Reporting Itens for Systematic Reviews and Meta-Analyses) and MOOSE (Meta-analysis Of Observational Studies in Epidemiology) guidelines were followed for data extraction. Also, we extracted from each study the dermoscopic criteria most commonly found in the lesions of LM/LMM. Results: This systematic review included 15 articles for qualitative analysis (a total of 2,012 lesions evaluated) and 7 for meta-analysis. In the bivariate model the mean sensitivity was 0.824 and the mean specificity was 0.835. The area under the curve was 0.889. Rhomboid structures, pseudonetwork, and homogeneous areas were the most frequent dermoscopic criteria associated with LM/LMM. Conclusion: These findings suggest that dermoscopy has good accuracy in the diagnosis of LM/LMM.